An Irish country love story - Taylor, Patrick, 1941- (Taylor, Patrick, 1941- Irish country novel., 2016)
"For decades, ever since the war, Number One Main Street, Ballybucklebo, has housed OReilly and his practice...It is to Number One that patients young and old come when they need a doctors care, for everything from the measles to a rare and baffling blood disease. An unexpected turn of events threatens to drive OReilly from his home for good, unless the entire village can rally behind their doctor and prove that love really can conquer all." -- Publisher.